2021
DOI: 10.1101/2021.10.17.464700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant-based production of SARS-CoV-2 antigens for use in a subunit vaccine

Abstract: The COVID-19 pandemic has brought to the forefront an urgent need for the rapid development of highly efficacious vaccines, particularly in light of the ongoing emergence of multiple variants of concern. Plant-based recombinant protein platforms are emerging as cost-effective and highly scalable alternatives to conventional protein production. Viral glycoproteins, however, are historically challenging to produce in plants. Herein, we report the production of plant-expressed wild-type glycosylated SARS-CoV-2 Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The His tag facilitated enrichment from the plant proteome but would need to be removed prior to the development of plant-based nanobody therapies for the treatment of human or other animal diseases. A recent example of production of RBD in planta exhibits suitable biochemical and antigenic features for use in a subunit vaccine platform (Demone, Nourimand et al 2021). We posit that molecular farming of nanobodies, and other biologicals is an under-developed area for cost savings and increased global access for the production of protein and small molecule therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The His tag facilitated enrichment from the plant proteome but would need to be removed prior to the development of plant-based nanobody therapies for the treatment of human or other animal diseases. A recent example of production of RBD in planta exhibits suitable biochemical and antigenic features for use in a subunit vaccine platform (Demone, Nourimand et al 2021). We posit that molecular farming of nanobodies, and other biologicals is an under-developed area for cost savings and increased global access for the production of protein and small molecule therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a modified nanobody with a scrambled RBD binding domain did not demonstrate the inhibition ability observed with the spike protein-targeted antibody, demonstrating the binding specificity of the interaction between the plant-produced RBDbinding nanobodies and the RBD. A recent example of production of RBD in planta exhibits suitable biochemical and antigenic features for use in a subunit vaccine platform (Dhama et al, 2020;Demone et al, 2021;Maharjan et al, 2021;Mamedov et al, 2021;Mardanova et al, 2021;Ceballo et al, 2022). Thus, scientists have shown that both the RBD antigen and RBDspecific antibodies can be generated in plants [Also see: (Diego-Martin et al, 2020)].…”
Section: Figurementioning
confidence: 99%